2006
DOI: 10.1161/01.hyp.0000196949.26088.3c
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Bicarbonate Cotransporter Polymorphisms Are Associated With Baseline and 10-Year Follow-Up Blood Pressures

Abstract: Abstract-The NaHCO 3 cotransporter gene (SLC4A5) on chromosome 2 encodes a protein that transports sodium and bicarbonate across the cell membrane and regulates cellular pH. The National Heart, Lung, and Blood Institute Family Blood Pressure Program found linkage of blood pressure-related traits to the chromosomal region containing SLC4A5 and phenotype associations with single nucleotide polymorphisms (SNPs) in this gene. However, the results were inconsistent over various phenotypes and SNPs. Nevertheless, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 29 publications
5
46
0
Order By: Relevance
“…shown that mutations in the SLC4A5 gene are associated with hypertension (2,7,18). Targeted disruption of NBCe2 in mice also results in hypertension (15) or neurological dysfunction (20).…”
Section: Summary and Conclusion Genetic Studies In Humans Havementioning
confidence: 99%
“…shown that mutations in the SLC4A5 gene are associated with hypertension (2,7,18). Targeted disruption of NBCe2 in mice also results in hypertension (15) or neurological dysfunction (20).…”
Section: Summary and Conclusion Genetic Studies In Humans Havementioning
confidence: 99%
“…Apically expressed NBCe2 in choroid plexus epithelia (Praetorius and Nielson, 2004) operates with a 1:3 stoichiometry (Millar and Brown, 2008), secreting HCO 3 -into the cerebrospinal fluid. Polymorphisms in the SLC4A5 gene locus have been genetically linked to hypertension (Barkley et al, 2004;Hunt et al, 2006), although none of the associated genetic changes alter the predicted NBCe2 peptide sequence. Alignment is based on a manually adjusted version of a sequence alignment that was originally generated by ClustalW (http://www.ebi.ac.uk/ Tools/clustalw2/index.html) using GenBank protein accession numbers for NBCe1-…”
Section: Nbce2 Molecular Functionmentioning
confidence: 99%
“…(36) A locus in chromosome 2 (2p14-2p13.1) (27,28) contains the SLC4A5 gene, which has been linked to increased blood pressure (BP). (6,29) SLC4A5 encodes the electrogenic sodium bicarbonate cotransporter 4 (NBCe2, formerly known as NBC4) (30), which has been significantly associated with high BP and/or SS (4,5,19,32,33). A related sodium bicarbonate cotransporter, NBCe1, encoded by SLC4A4, is located in the human renal proximal tubule (RPT) (21), medullary thick ascending limb (mTAL), and collecting duct (7).…”
mentioning
confidence: 99%